Маркетингові аспекти формування збалансованого портфеля бізнесів підприємства - Солнцев, С. О.; Яворська, К. Ю. (Видавництво Львівської політехніки, 2012)
Розкрито сутність категорії “збалансований портфель бізнесів” та розглянуто його види на підприємстві. Запропоновано групу критеріїв для оцінювання збалансованості складу та структури портфеля залежно від типу структурних підрозділів, що його формують. Виділено маркетингові аспекти процесу формування збалансованого портфеля компанії. Проаналізовані підходи до виділення стратегічних бізнес-одиниць портфеля. Запропоновано комплексну процедуру маркетингового управління портфелем бізнесів підприємства. In the article the essence of “balanced businesses portfolio” was revealed and its enterprise’s types were examined. Balanced business portfolio is a set of different field of businesses of its own life cycle’s stage, needs certain resource structure, responsible for a certain income and has its own marketing role in a portfolio that aims to achieve the strategic company’s goals in general. A group of evaluation criteria to estimate the business portfolio structure and composition balance depending on types of its strategic business unit was suggested. There are three main types of SBU: enterprise, brand, product. Depends on SBU’s type different criteria groups were suggested. Marketing portfolio formation aspects were highlighted. Therefore cases when services form third product level can be independent SBU were justified. The complex process of business portfolio marketing management was suggested. According to developed process there in general there are four stages of business portfolio management: business portfolio structuring, business portfolio’s balance evaluation, balanced business portfolio formation, balanced portfolio realization.
Marketing formation aspects enterprise’s balanced business portfolio
Keywords: портфель бізнесів; стратегічна одиниця бізнесу; збалансованість портфеля; оцінювання портфеля; діагностування; business portfolio; strategic business unit; balanced business portfolio; portfolio estimation